2019
DOI: 10.1177/2040206619826265
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti-human immunodeficiency virus activity of substituted (o,o-difluorophenyl)-linked-pyrimidines as potent non‐nucleoside reverse transcriptase inhibitors

Abstract: With the worldwide number of human immunodeficiency virus positive patients stagnant and the increasing emergence of viral strains resistant to current treatment, the development of novel anti-human immunodeficiency virus drug candidates is a perpetual quest of medicinal chemists. Herein, we report a novel group of diarylpyrimidines, non-nucleoside reverse transcriptase inhibitors, which represents an important class of current anti-human immunodeficiency virus therapy. Series of diarylpyrimidines containing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In the study reported by Cechová et al ., a new group of diarylpyrimidine reverse transcriptase inhibitors was synthesized [27] . The 20 compounds in the series were tested for cytoprotection against reverse transcriptase mutant strains (K103N, Y181C) and wild‐type Human Immunodeficiency Virus‐1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study reported by Cechová et al ., a new group of diarylpyrimidine reverse transcriptase inhibitors was synthesized [27] . The 20 compounds in the series were tested for cytoprotection against reverse transcriptase mutant strains (K103N, Y181C) and wild‐type Human Immunodeficiency Virus‐1.…”
Section: Resultsmentioning
confidence: 99%
“…synthesized. [27] The 20 compounds in the series were tested for cytoprotection against reverse transcriptase mutant strains (K103N, Y181C) and wild-type Human Immunodeficiency Virus-1. Among the compounds tested, the ones that showed the most promise were compounds 9, with EC 50 = 2 nM, 10 with EC 50 = 3 nM and 11 with EC 50 = 4 nM (Figure 6).…”
Section: Anti-hiv Activitymentioning
confidence: 99%